Administrative business law as a structural element of administrative law system: foreign experience and national peculiarities - Мельник, Роман Сергійович; Петров, Євген Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The essence and peculiarities of administrative business law of Germany are disclosed in the light of comparative legal research. The process of formation and development of native administrative business law is also researched.